If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -6 = 37 Reorder the terms: -6 + n = 37 Solving -6 + n = 37 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + n = 37 + 6 Combine like terms: -6 + 6 = 0 0 + n = 37 + 6 n = 37 + 6 Combine like terms: 37 + 6 = 43 n = 43 Simplifying n = 43
| (21b-6)-5(4b+1)=-4 | | x*.54=210 | | K/7=2 | | x*.54=250 | | 2/3x-7/3=6 | | x*.7=250 | | 7x(4+3-5)= | | x*.16=40 | | 9x+9=45+x | | 5(x-4)=2x+5(x-2) | | x*.44=110 | | 8x=90+2x | | 16(3x)=64(x+5) | | h(x)=(2x-6) | | 28-0.3=0.74-12 | | 9(w-6)= | | 8w^2-2122w+20000=0 | | 2d+4=10+6d | | 11-7*2+3= | | x*.16=4 | | (x^3)+(5x^2)-x-5=0 | | 8/7y-4/7 | | 8x+10=6x-12 | | x*.15=3 | | 4c=2c+9 | | 7.37x+64=54.3169+8x | | 6/7x-3/7=9 | | 6.95x+34.75=69.5 | | 99-w=208 | | 8.6a+11=114.2 | | 21=8d-9(2d+1) | | x^2+14x-106=0 |